Calcipotriol/betamethasone dipropionate ointment in mild‐to‐moderate paediatric psoriasis: long‐term daily clinical practice data in a prospective cohort. (6th June 2014) - van Geel, M.J.; Mul, K.; Oostveen, A.M.; van de Kerkhof, P.C.M.; de Jong, E.M.G.J.; Seyger, M.M.B.
Summary Background Psoriasis in children has a significant negative impact on the quality of life (QoL) and effective treatment can improve this. The two‐compound ointment calcipotriol 50 μg g−1 and betamethasone dipropionate 0·5 mg g−1 is an effective treatment option for moderate‐to‐severe psoriasis in adults. Objectives To study prospectively the effectiveness and safety of calcipotriol/betamethasone dipropionate ointment in paediatric patients with mild‐to‐moderate plaque psoriasis in daily clinical practice and to investigate the influence on QoL. Methods Data were obtained from a prospective, longitudinal paediatric psoriasis registry, called Child‐CAPTURE. Severity was assessed using the Psoriasis Area and Severity Index (PASI) and body surface area (BSA). The Children's Dermatology Life Quality Index (CDLQI) was used to assess QoL and visual analogue scores (VAS) for pain and itch were collected. For safety data the number of (serious) adverse events was recorded. Results Seventy‐three patients (mean age 10·8 years, range 3–18) were treated for a median time of 35·0 weeks (range 1·0–176·0). At week 12, mean PASI decreased 15·4% (from 5·2 to 4·4), BSA barely changed, and median CDLQI decreased significantly from 5·5 to 4·0. VAS scores for pain and itch declined. At week 24, mean PASI decreased to 4·3 (17·3%). No related serious adverse events were observed. Conclusions In this daily clinical practice study in paediatric psoriasis, calcipotriol/betamethasone dipropionate ointment initially improved mild‐to‐moderate psoriasis and then maintained its effect. In addition, it improved QoL, with few adverse events.